2011
DOI: 10.1002/jcp.22576
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol inhibits LPS‐induced maturation and inflammatory response of human monocyte‐derived dendritic cells

Abstract: Honokiol (HNK) is a phenolic compound isolated from the bark of houpu (Magnolia officinalis), a plant widely used in traditional Chinese and Japanese medicine. While substantial evidence indicates that HNK possesses anti-inflammatory activity, its effect on dendritic cells (DCs) during the inflammatory reaction remains unclear. The present study investigates how HNK affects lipopolysaccharide (LPS)-stimulated human monocyte-derived DCs. Our experimental results show that HNK inhibits the inflammatory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 73 publications
4
30
0
Order By: Relevance
“…Having shown that crp-CD14 + cells differentiate into imdDCs, the ability of these cells to respond to an inflammatory stimulus (LPS, a TLR4 ligand that induces the expression of mdDC maturation markers and cytokines/chemokines production) was analyzed [20], [21]. Crp- and frh-imdDCs (5×10 5 viable cells based on Trypan Blue exclusion assay) were treated with LPS and analyzed for the expression of activation markers (CD40, CD80, CD83 and CD86) at 0, 6, 24 and 48 hours post-treatment (hpt) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that crp-CD14 + cells differentiate into imdDCs, the ability of these cells to respond to an inflammatory stimulus (LPS, a TLR4 ligand that induces the expression of mdDC maturation markers and cytokines/chemokines production) was analyzed [20], [21]. Crp- and frh-imdDCs (5×10 5 viable cells based on Trypan Blue exclusion assay) were treated with LPS and analyzed for the expression of activation markers (CD40, CD80, CD83 and CD86) at 0, 6, 24 and 48 hours post-treatment (hpt) [22].…”
Section: Resultsmentioning
confidence: 99%
“…The partial or complete reversal of production of IL-12p70 by LPS-activated DCs has been linked to stimuli as diverse as prostaglandins, histamine, alkaloids and phenolic products. [58][59][60][61] In relation to CysLT, in terms of cytokines, the results are contradictory. Machida et al 40 described in Derf-pulsed DCs from bone marrow precursors how antagonists of CysLTR1 led to the enhancement of IL-12p40 while IL-10 was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…In murine models, adoptive transfusions of tolerogenic DCs could obtain an expansion of Tregs and reduced allotransplant sensitization in different types of transplants [63][64][65]. Other approaches explored in animal models comprised the inhibition of DCs maturation with agents such as vascular-endothelial growth factor [66], IL-10 [67], laquinimoid [68], shikonin [69], honokiol [70], immunoglobulins [71] and phosphodiesterase inhibitors [72]. Alternatively, drugs favoring the production of Tregs have been employed.…”
Section: Manipulation Of Dcs In Allotransplant Recipientsmentioning
confidence: 99%